Desalination of brackish water using renewable energy - Hasan, Mohammad Tasnimul; Islam, Mohammad Asadul; Haider, Saad Bin; Irtiza, Aseer (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.